Status of nursing documentation types in Indonesia and their association with nurse characteristics: A cross-sectional survey - Ernawati; Permaida (Belitung Nursing Journal, 2025)
Background: Nursing documentation is essential for legal accountability, continuity of care, and patient safety. While electronic nursing documentation offers advantages such as improved clarity, efficiency, and reduced workload, no nationwide study has examined which documentation types are most used in Indonesia or how nurse characteristics influence these choices. Addressing this gap is critical for guiding policy and supporting the transition to digital systems. Objective: This study aimed to determine the types of nursing documentation systems most used by nurses in Indonesia and to examine nurse characteristics associated with documentation type. Methods: A cross-sectional online survey was conducted in March 2023 among 894 nurses from 34 of Indonesia’s 38 provinces. Data collected included sociodemographic characteristics, workplace settings, and documentation types (paper-based, electronic, or combination). Associations between nurse characteristics and documentation types were analyzed using the Kruskal–Wallis test, with post-hoc Mann–Whitney U tests comparing the distribution of education levels between each pair of documentation-type groups. Results: Most participants were women (75.8%), held a diploma in nursing (53.5%), had over 12 years of work experience (35.3%), and worked in tertiary healthcare facilities (43.3%). Paper-based documentation was predominant (66.6%), followed by combination systems (24.7%) and electronic systems alone (8.7%). Paper-based use was slightly higher in Western Indonesia (66.8%) compared to Eastern Indonesia (64.8%). Education level was significantly associated with documentation type (p = 0.014). Post-hoc analysis showed that nurses using electronic documentation had higher education levels than those using paper-based (p = 0.006) or combination systems (p = 0.006), with electronic documentation most common among nurses holding a Master’s/Specialist degree (28.1%). No significant associations were found with sex, work experience, career level, service level, healthcare unit, or region. Conclusion: Paper-based nursing documentation remains dominant in Indonesia, with limited adoption of electronic systems. Higher educational attainment is associated with greater use of electronic documentation, highlighting the need for improved computer literacy training, infrastructure investment, and institutional and governmental support to facilitate the transition to digital documentation.